2020
DOI: 10.1111/1475-5890.12240
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Children's Experiences of Home Learning during the COVID‐19 Lockdown in England*

Abstract: This paper combines novel data on the time use, home-learning practices and economic circumstances of families with children during the COVID-19 lockdown with pre-lockdown data from the UK Time Use Survey to *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
276
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(356 citation statements)
references
References 19 publications
16
276
1
10
Order By: Relevance
“…Question 1 about general emotional wellbeing and question 2 about how work and/or study impacted on mood and feelings provided some mothers with the opportunity to elaborate on concerns about childcare and/or homeschooling and how work had impacted on their capacity to juggle. No relevant information was identi ed in the social life (3), daily routines (4), society open -up (6) questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Question 1 about general emotional wellbeing and question 2 about how work and/or study impacted on mood and feelings provided some mothers with the opportunity to elaborate on concerns about childcare and/or homeschooling and how work had impacted on their capacity to juggle. No relevant information was identi ed in the social life (3), daily routines (4), society open -up (6) questions.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the associated stress some mothers reduced expectations or gave up home-schooling altogether to protect theirs and their family wellbeing. Research by the Institute for Fiscal Studies, UK has warned about how varying degrees and quality of access to home learning are deepening inequalities (Andrew et al, 2020c) and call for research in to understanding the factors implicated. Our ndings revealed some of the factors which could be included in future investigations on the impact of caring for children and home learning while working on children and families and intervention design.…”
Section: Discussionmentioning
confidence: 99%
“…While deemed necessary for health and safety reasons, school closures likely carry costs related to learning outcomes. Recent studies have demonstrated that students exposed to distance learning have made "little or no progress while learning from home" according to progressions in test scores, and that students from disadvantaged socio-economic backgrounds may face even steeper declines in learning outcomes 2,7,15 . Throughout the start of the 2020-2021 school year, not all students in the U.S. have been exposed to distance learning.…”
Section: Discussionmentioning
confidence: 99%
“…Given evidence that school closures are detrimental to educational performance, particularly for students of disadvantaged backgrounds 2,7,[15][16][17][18][19][20] , the large socio-economic, geographic, and demographic disparities in exposure to distance learning suggest that the COVID-19 pandemic is likely to exacerbate inequalities in learning outcomes across the U.S.…”
Section: This Study Introduces and Analyzes A Us School Closure And Dmentioning
confidence: 99%
“…However, there are concerns of heightened parenting stress and lowered parenting quality in the COVID-19 pandemic [ 21 , 22 , 23 ]. Spending more hours on childcare each day while managing their work remotely from home [ 24 ], along with other pandemic-related factors such as employment loss, financial insecurity, lack of help from external families, and a dearth of leisure time, may increase the risk of parental burnout [ 23 ]. Increased parenting stress can provoke negative parenting behaviors such as harsh parenting [ 21 , 25 ] and verbal hostility toward children [ 26 ].…”
Section: Introductionmentioning
confidence: 99%